La CIDH es Necesaria y hay Que Apoyarla - Masís-Iverson, Daniel (Hemisferio - Revista del Colegio Interamericano de Defensa, 2017)
This article approaches the 2016 financial crisis of the IACHR, the work of the IACHR itself, and doubts that may exist regarding the latter, and how to deal with them